Auditors' Willingness to Advocate Client-Preferred Accounting Principles - Shafer, William E. (Journal of business ethics, 2004)
This paper argues that independent auditors have lost sight of their obligation to be truly impartial, and have increasingly adopted an attitude of client advocacy. We argue that auditors have a professional obligation to go beyond merely passing judgment on whether client accounting methods are acceptable under GAAP, and to judge whether the principles adopted are the most appropriate under the circumstances. We then review recent evidence which suggests that auditors have abandoned this objective in favor of advocating client-preferred principles. The results of a survey of public accountants employed by small CPA firms indicates that, in a scenario in which an auditor did not feel that the client's accounting treatment was the most appropriate under the circumstances but it was recognized as an acceptable alternative under GAAP, advocacy of the client-preferred approach is considered appropriate and is very likely to occur in practice. In less subtle cases (e.g., when the auditor did not feel that the client's treatment provided the best reflection of the economic substance of the underlying transactions), survey participants as a group were ambivalent regarding the appropriateness of client advocacy, and felt that subordination of judgment was likely to occur in practice. The results also indicate that engagement risk, or the risk that the firm will be harmed by aggressive behavior, affects judgments of both the appropriateness and likelihood of subordination of judgment. These findings suggest that auditors have adopted an ideology of client advocacy, within the constraints of engagement risk.